Eficacia del extracto de caléndula officinalis para tratamientos e caninos con dermatitis pruriginosa de la cuidad de Popayán (2022)
Pruritic dermatitis is a chronic skin disease of dogs, which is of great concern to pet owners when they no longer see improvement in their dogs. The purpose of this work was to carry out a treatment as an adjuvant for pruritic dermatitis with calendula officinalis extract, applying phytotherapy in patients, this work was carried out at the Terranova Veterinary Clinic in the city of Popayan, during the first period of the year. 2022. For the above, it was taken into account that the canines must be adults of any race and sex; as well as previous reports and investigations of the symptoms presented by patients with dermatitis will be taken into account; Likewise, a skin examination (general observation, inspection and observation of the different pathologies found in the skin of the canines that made up this study) was performed on each patient who entered the clinic. In the methodological process, 25 canes with pruritic dermatitis problems were selected. Finally, the results were analyzed, having an effectiveness of 56%, highlighting the most relevant cases, making known alternative medicine with calendula officinalis extract to treat dermatitis lesions, which is one of the most registered in the veterinary clinic today. today and thereby implement this type of natural treatment in our patients.